The Effects of Inflation and Devaluation on the Assessment of Investment Flows - Solé Madrigal, Roberto (2012)
Being that today both inflation and the devaluation of the currencies are a constant in all the world’s economies, and the developed economies do not escape this even when the rates are “of a digit”, it is important to take into account their effects over time in a project for its evaluation and impact on metrics traditionally used: Net Present Value (NPV) and Internal Rate of Return (IRR).Refine evaluation techniques in a consistent way with the economic reality, is becoming increasingly imperative, that allows the financial evaluator to clearly interpret them for a correct decision. Inflation or devaluation apparently “low” over the years, may have a “high” impact on cash flows, which could be misleading to an investor to ignore them and thus take a wrong decision.